#influenced! The impact of social media influencing on self-esteem and the role of social comparison and resilience - Rüther, Lale; Jahn, Josephine; Marksteiner, Tamara (Frontiers in Psychology, 2023)
Social media influencers (SMIs) are online personas that acquire significant audiences on social networking sites (SNS) and have become a prevalent part of social media. Previous research indicates potentially detrimental effects of social media use on mental well-being, however, little is known about whether, how, and for whom online comparisons with SMIs lead to adverse psychological effects. In this study, we investigate the impact of positivity-biased images of female SMIs on the state self-esteem of female participants while considering social comparison processes as mediating and individual resilience as moderating factors. Regression analyses showed that acute exposure to positivity-biased SMI images led to upward social comparisons, which in turn predicted lower state self-esteem. Thus, results revealed a significant mediating effect of social comparisons on the association between image type and state self-esteem. However, when observing the direct effect of image type on state self-esteem, we found that the exposure to positivity-biased SMI images unexpectedly led to higher overall levels of state self-esteem relative to the control group. In light of contemporary social comparison literature, subsequent post-hoc analyses suggest that exposure to SMI images in this study may have prompted both contrastive and assimilative upwards comparisons, leading to varying consequences for distinct self-esteem dimensions, ultimately manifesting in the observed suppression effect. Resilience was not found to moderate the proposed associations. Thus, the findings of this study offer new insights into the impact of SMIs on individuals’ self-evaluations online, challenging previous assumptions, and suggest a need for further examination.